Prevalence of periodontal diseases: Latin America and the Caribbean Consensus 2024 - Carvajal, Paola (2024)
The aim of this review was to update knowledge about the prevalence of periodontitis in Latin America and the Caribbean. A critical review of was performed of all cross-sectional or cohort studies selected, pertaining to the region, and thirty-five studies conducted in 12 countries were selected. The countries with nationally representative studies were Brazil, Chile, Colombia, and Uruguay. The prevalence of periodontal disease or need for periodontal treatment varied between the different studies and countries depending on the age group, the methodology used, and the case definition. The prevalence of severe periodontitis aged between 5.8% and 49.7% in adults. In adolescents, the prevalence of moderate to severe periodontitis was 15.3%. Furthermore, a high prevalence of gingival bleeding in adolescents was reported. When analyzing the studies that used the Community Periodontal Index (CPI), Centers for Diseases Control and American Academy Periodontology (CDC/AAP) case definition, it was observed that as the age of the individuals analyzed increased, the prevalence of periodontal disease also increased. Whereas this rereview revealed that although the number of regional and nationally representative studies that analyzed the prevalence of periodontitis has risen in recent years, their methodological heterogeneity prevents global conclusions to be drawn concerning the region. Therefore, this ratifies the need to generate alliances between countries with the purpose of joining individual efforts to achieve collective goals which, among other objectives, will translate into conducting multicenter studies. These studies would allow description and monitoring of the epidemiological behavior of periodontitis in Latin America and the Caribbean.